Attention capture by abrupt onsets: re-visiting the priority tag model - Sunny, Meera M.; von Muhlenen, Adrian (Frontiers in Psychology, 2013)
Abrupt onsets have been shown to strongly attract attention in a stimulus-driven, bottom-up manner. However, the precise mechanism that drives capture by onsets is still debated. According to the new object account, abrupt onsets capture attention because they signal the appearance of a new object. Yantis and Johnson (1990) used a visual search task and showed that up to four onsets can be automatically prioritized. However, in their study the number of onsets co-varied with the total number of items in the display, allowing for a possible confound between these two variables. In the present study, display size was fixed at eight items while the number of onsets was systematically varied between zero and eight. Experiment 1 showed a systematic increase in reactions times with increasing number of onsets. This increase was stronger when the target was an onset than when it was a no-onset item, a result that is best explained by a model according to which only one onset is automatically prioritized. Even when the onsets were marked in red (Experiment 2), nearly half of the participants continued to prioritize only one onset item. Only when onset and no-onset targets were blocked (Experiment 3), participants started to search selectively through the set of only the relevant target type. These results further support the finding that only one onset captures attention. Many bottom-up models of attention capture, like masking or saliency accounts, can efficiently explain this finding.